AN INTRODUCTION OF CREDITORS RIGHTS IN THE ALBANIAN INSOLVENCY LAW - Skara, Gentjan; Zaimi, Jetnor; Nezha, Kelmend (European Scientific Journal, ESJ, 2012)
All the insolvency proceedings in Albania are governed by the Insolvency Law 2002. According to this law, insolvency proceedings can be open against physical and legal entities as defined by the Albanian Company law. However, certain entities – mainly public bodies - are excluded from the insolvency proceedings. This paper provides the creditors right in Albanian Insolvency Law. After providing enough information, about the grounds of opening the insolvency procedure and subjects which are legitimated to make request to open the insolvency proceedings, it analyze the creditors right to request the opening insolvency proceedings and types creditors. Then the paper will conclude with the review of creditors’ claim according to Albanian insolvency law.